New reference ranges for interpreting forced expiratory manoeuvres in infants and implications for clinical interpretation: a multicentre collaboration. Issue 3 (2nd November 2015) - Lum, Sooky; Bountziouka, Vassiliki; Wade, Angela; Hoo, Ah-Fong; Kirkby, Jane; Moreno-Galdo, Antonio; de Mir, Ines; Sardon-Prado, Olaia; Corcuera-Elosegui, Paula; Mattes, Joerg; Borrego, Luis Miguel; Davies, Gwyneth; et al.
Abstract : The raised volume rapid thoracoabdominal compression (RVRTC) technique is commonly used to obtain full forced expiratory manoeuvres from infants, but reference equations derived from 'in-house' equipment have been shown to be inappropriate for current commercially available devices. Aim: To explore the impact of equipment differences on RVRTC outcomes, derive robust equipment-specific RVRTC reference ranges and investigate their potential clinical impact on data interpretation. Method: RVRTC data from healthy subjects using Jaeger BabyBody or the 'Respiratory Analysis Software Program, RASP' systems were collated from four centres internationally. Data were excluded if gestational age <37 weeks or birth weight <2.5 kg. Reference equations for RVRTC outcomes were constructed using the LMS (lambda–mu–sigma) method, and compared with published equations using data from newborn screened infants with cystic fibrosis (CF). Results: RVRTC data from 429 healthy infants (50.3% boys; 88% white infants) on 639 occasions aged 4–118 weeks were available. When plotted against length, flows were significantly higher with RASP than Jaeger, requiring construction of separate equipment-specific regression equations. When comparing results derived from the new equations with those from widely used published equations based on different equipments, discrepancies in forced expiratory volumes and flows of up to 2.5 z-scores were observed, the magnitude of which increased with age. According to published equations, 25% of infants with CF fell below the 95% limits of normal for FEV0.5, compared with only 10% when using the new equations. Conclusions: Use of equipment-specific prediction equations for RVRTC outcomes will enhance interpretation of infant lung function results; particularly during longitudinal follow-up.